SEROPREVALENCE OF HEPATITIS-B VIRUS IN MID AND FAR WESTERN REGION IN NEPAL - S, Khan; P, Singh; A. H., Siddiqui; M, Ansari (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2013)
Hepatitis B is significant health problems that might involve the late sequel of liver cirrhosis and hepatocellular carcinoma. The present study aimed to know the seroprevalence of hepatitis B virus (HBV) in mid and far western region in Nepal with various clinical conditions. This was a retrospective study conducted in mid and far western region in Nepal, which was performed in the Central Laboratory of Microbiology at Nepalgunj Medical College and Teaching Hospital, Banke, Nepal during the period of September 2010 to April 2012. The serum samples were tested for Hepatitis B surface Antigen (HBsAg) by Sandwich immunoassay. Total 7010 patients including 43.72% male and 56.28% female were tested for HBsAg. Of them, 135 were positive and 6875 were negative. In 135 positive cases 84 (62.22%) were male and 51 (37.77% )were female. In 6875 negative cases 2981 were male and 3894 were female. The seroprevalence rate of HBV was 1.93% in mid and far western region in Nepal. Seroprevalence of HBV seems to be higher in male then the female; it was 2.75% in male and 1.29% in female. The study revealed that the seroprevalence of HBV was alarmingly higher in such a population, which probably reflects a high background prevalence of HBV infections should be taken into consideration and Implementation of community-based preventive measures and improved strategies for safe blood supply might prove useful to decrease the seroprevalence.
Keywords: seroprevalence; hepatitis B virus; Hepatitis B surface Antigen